2019
DOI: 10.1111/aec.12747
|View full text |Cite
|
Sign up to set email alerts
|

Does land use change influence predation of bird nests?

Abstract: Worldwide, many areas of agricultural land which were once covered with native vegetation have been converted to tree plantations. Such landscape transformation can influence the dynamics of wildlife populations through, for example, altering rates of predation (e.g. predation of nests of birds). Nest predation can influence reproductive success and, in turn, may alter populations by affecting juvenile recruitment. We quantified predation of bird nests in woodland remnants surrounded by two types of land use, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Landscape modification affects particular taxa and produces variation at the trophic levels (e.g., da Silva & Rossa‐Feres, 2017), including disappearance of dispersal agents (e.g., Mortelliti & Lindenmayer, 2015). There is evidence that, due to a lack of resources from the original habitats, landscape with afforestation increases nest predation of birds by generalists (e.g., Okada et al, 2019). This can reduce both abundance and richness of these dispersal agents (Phifer et al, 2017; Terborgh et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Landscape modification affects particular taxa and produces variation at the trophic levels (e.g., da Silva & Rossa‐Feres, 2017), including disappearance of dispersal agents (e.g., Mortelliti & Lindenmayer, 2015). There is evidence that, due to a lack of resources from the original habitats, landscape with afforestation increases nest predation of birds by generalists (e.g., Okada et al, 2019). This can reduce both abundance and richness of these dispersal agents (Phifer et al, 2017; Terborgh et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Among wildlife species, birds are highly sensitive to habitat changes, and can therefore act as indicators of habitat changes [12,13]. With the advancement of urbanization, habitat reduction and habitat fragmentation caused by economic development and human activities are having increasing impacts on bird communities [14][15][16][17], which also impacts species composition [18][19][20], predation behaviors [21], and migration paths. Studies have found that the number of birds in North America has decreased by around 29% since 1970, equivalent to nearly 3 billion birds, with habitat loss being the main reason for this steep decline [2].…”
Section: Introductionmentioning
confidence: 99%